2014
DOI: 10.1371/journal.pone.0091466
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of a Multiple Recurrent Muscle-Invasive Urothelial Carcinoma of the Bladder by Deep Sequencing

Abstract: Urothelial carcinoma of the bladder (UCB) is one of the commonly diagnosed cancers in the world. The UCB has the highest rate of recurrence of any malignancy. A genome-wide screening of transcriptome dysregulation between cancer and normal tissue would provide insight into the molecular basis of UCB recurrence and is a key step to discovering biomarkers for diagnosis and therapeutic targets. Compared with microarray technology, which is commonly used to identify expression level changes, the recently developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 74 publications
3
26
0
Order By: Relevance
“…An invasion-associated four-gene signature including Latrophilin-1 obtained from the NCI-60 cell line panel has significant prediction in non-small cell lung cancer (NSCLC) [40]. A genome-wide screen between a recurrent muscle-invasive cis-platin-resistant urothelial bladder carcinoma and its adjacent non-tumor tissue found cancer-associated alternative splicing with differential exon usage for LPHN2 [153]. Linkage studies have revealed numerous Latrophilin-3 loss-of-function mutations in breast, lung, ovarian, and prostate cancers [21].…”
Section: Families Of Adhesion Gpcr In Tumorigenesismentioning
confidence: 99%
“…An invasion-associated four-gene signature including Latrophilin-1 obtained from the NCI-60 cell line panel has significant prediction in non-small cell lung cancer (NSCLC) [40]. A genome-wide screen between a recurrent muscle-invasive cis-platin-resistant urothelial bladder carcinoma and its adjacent non-tumor tissue found cancer-associated alternative splicing with differential exon usage for LPHN2 [153]. Linkage studies have revealed numerous Latrophilin-3 loss-of-function mutations in breast, lung, ovarian, and prostate cancers [21].…”
Section: Families Of Adhesion Gpcr In Tumorigenesismentioning
confidence: 99%
“…Thus, Numb PRR L promoted proliferation but not differentiation in murine embryonic carcinoma cells, whereas Numb PRR S promoted differentiation but not proliferation . Recently, global profiling identified Numb exon 12 inclusion as a frequent splicing event in human non‐small‐cell lung cancer and in invasive bladder cancer . Furthermore, expression of Numb PRR L was increased in tumors compared with normal tissues and correlated with poor prognosis.…”
mentioning
confidence: 99%
“…CD44s is the major isoform expressed in UMUC3 cells, and was able to fully rescue CD44 knockdown. Interestingly, transcriptome analysis of recurrent muscle invasive bladder cancer patients compared to newly diagnosed patients revealed increased CD44 expression (Choi et al, 2014; Zhang et al, 2014). Moreover, we found that TIAM1, which binds the CD44s cytoplasmic domain and functions as a GEF for Rac1 (Terawaki et al, 2010), is the critical intracellular effector required for stimulation of invasion.…”
Section: Discussionmentioning
confidence: 99%